Are Asians comfortable with discussing death in health valuation studies? A study in multi-ethnic Singapore - Wee, Hwee-Lin (BioMed Central, 2006)
BACKGROUND: To characterize ease in discussing death (EID) and its influence on health valuation in a multi-ethnic Asian population and to determine the acceptability of various descriptors of death and "pits"/"all-worst" in health valuation. METHODS: In-depth interviews (English or mother-tongue) among adult Chinese, Malay and Indian Singaporeans selected to represent both genders and a wide range of ages/educational levels. Subjects rated using 0–10 visual analogue scales (VAS): (1) EID, (2) acceptability of 8 descriptors for death, and (3) appropriateness of "pits" and "all-worst" as descriptors for the worst possible health state. Subjects also valued 3 health states using VAS followed by time trade-off (TTO). The influence of sociocultural variables on EID and these descriptors was studied using univariable analyses and multiple linear regression (MLR). The influence of EID on VAS/TTO utilities with adjustment for sociocultural variables was assessed using MLR. RESULTS: Subjects (n = 63, 35% Chinese, 32% Malay, median age 44 years) were generally comfortable with discussing death (median EID: 8.0). Only education significantly influenced EID (p = 0.045). EID correlated weakly with VAS/TTO scores (range: VAS: -0.23 to 0.07; TTO: -0.14 to 0.11). All subjects felt "passed away", "departed" and "deceased" were most acceptable (median acceptability: 8.0) while "sudden death" and "immediate death" were least acceptable (median acceptability: 5.0). Subjects clearly preferred "all-worst" to "pits" (63% vs. 19%, p < 0.001). CONCLUSION: Singaporeans were generally comfortable with discussing death and had clear preferences for several descriptors of death and for "all-worst". EID is unlikely to influence health preference measurement in health valuation studies.